AKTIVITAS EKSTRAK ETANOL DAUN KEDONDONG (Spondias pinnata (L.F) Kurz.) TERHADAP ANTIBODI IgM DAN IgG PADA MENCIT BALB/C YANG DIINDUKSI VAKSIN HEPATITIS B - Maria Ulfah; Penni Dwi Royani; Rita Febrianti_Lidya Putra (Universitas Wahid Hasyim Semarang, 2018)
ABSTRACTAntibodies play a role in maintaining the body’s immune system from various microorganism. When the body experiences an imbalance, the body needs a compound that can increase antibodies. Flavonoids, polyphenols and alkaloids can increase antibodies. Flavonoids, polyphenols and alkaloids can increase antibodies. Ethanol extract of kedondong leaves contains compounds of flavonoid, alkaloids, and polyphenols. The purpose of this study was to determine the immunomodulatory activity of ethanol extract in IgM and IgG antibodies in balb /c mice induced by hepatitis B vaccine. Ethanol extract of kedondong leaves was macerated with 96% ethanol. The doses of the concentration of ethanol extract of kedondong leaves used were 5, 10 and 20% p.o for 46 days and vaccination was carried out on the 7th, 28th and 43rd days. Positive control was used with levamisole at a dose of 0.45mg / 20gBB by p.o. Analysis of Optical Density (OD) IgM and IgG on days 14, 35 and 46 using Friedman and Mann Whitney statistical tests. The results showed that the ethanol extract of kedondong leaves had activity of increasing IgM and IgG antibodies at concentrations of 5, 10 and 20% on days 14, 35 and 46 and contained flavonoids, alkaloids and polyphenols.Keywords: Hepatitis B Vaccine, IgM, IgG, Optical Density (OD)